2017
DOI: 10.1002/acp.3338
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in School‐age Children: Influence of Age, Gender, School Type and Parental Education

Abstract: Summary: This study aimed to evaluate whether age, gender, type of school and parental education could predict executive performance in school‐age children. Unconstrained, phonemic and semantic verbal fluency tasks (n = 402), as well as the Hayling Sentence Completion Test (n = 275) and the Random Number Generation task (n = 274) were administered to typically developing 6‐to‐12‐year‐old children. A hierarchical regression analysis was performed (p ≤ 0.05). The most significant explanatory models involved chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
15
1
6
Order By: Relevance
“…These results are in agreement with study of Rosenthal et al (2013) who found impairment in EF with increasing age among children with autism spectrum disorder using BRIEF (parent report) also, driven by MI scales (initiate, working memory and organization of materials). However, general agreement in the literature is that EF (mainly cognitive flexibility, working memory and inhibition) are improving from childhood to adulthood among people with typical development (Jacobsen, de Mello, Kochhann, & Fonseca, 2017) as well as among people with ID (Hartman et al, 2017). A potential reason why the same trend has not been found in our study is because in the group of older children (15-18 years of age), there were mostly children with moderate ID (more than 60 per cent) whose EF's were significantly more impaired in comparison with children with mild ID.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with study of Rosenthal et al (2013) who found impairment in EF with increasing age among children with autism spectrum disorder using BRIEF (parent report) also, driven by MI scales (initiate, working memory and organization of materials). However, general agreement in the literature is that EF (mainly cognitive flexibility, working memory and inhibition) are improving from childhood to adulthood among people with typical development (Jacobsen, de Mello, Kochhann, & Fonseca, 2017) as well as among people with ID (Hartman et al, 2017). A potential reason why the same trend has not been found in our study is because in the group of older children (15-18 years of age), there were mostly children with moderate ID (more than 60 per cent) whose EF's were significantly more impaired in comparison with children with mild ID.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, a fin de poder constatar esta hipótesis sería necesario evaluar poblaciones de niños más pequeños, así como realizar estudios longitudinales que permitan observar el seguimiento de los cambios en el desarrollo. Además, sería necesario ampliar la muestra considerando participantes de diferentes estratos socio-económicos, ya que existen variables sociales que impactan diferencialmente en el desarrollo lingüístico Jacobsen, et al, 2017;Jacobsen, et al, 2016).…”
Section: Discussionunclassified
“…La realización de las tareas de fluidez verbal depende de procesos léxico-semán-ticos y de las funciones ejecutivas que se desarrollan durante los años de escolaridad y alcanzan los niveles adultos durante la adolescencia (Anderson, Anderson, Northram, Jacobs, & Catroppa, 2001;Bolla, Lindgren, Bonaccorsy, & Bleecker, 1990;Jacobsen, de Mello, Kochhann, & Fonseca, 2017;Riva, Nichelli, & Devoti, 2000;Ruff, Light, Parker, & Levin, 1997;Stuss et al, 1998). Las funciones ejecutivas son procesos cognitivos que permiten sostener y manipular información, actuar y responder en función del contexto, autorregular la conducta, inhibir respuestas o diferirlas, organizar un plan estratégico de acción en función de un objetivo y elaborar una representación mental de la tarea.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…These results are in agreement with study of Rosenthal et al (2013) who found impairment in EF with increasing age among children with autism spectrum disorder using BRIEF (parent report) also, driven by MI scales (initiate, working memory and organization of materials). However, general agreement in the literature is that EF (mainly cognitive flexibility, working memory and inhibition) are improving from childhood to adulthood among people with typical development (Jacobsen, de Mello, Kochhann, & Fonseca, 2017) as well as among people with ID (Hartman et al, 2017). A potential reason why the same trend has not been found in our study is because in the group of older children (15-18 years of age), there were mostly children with moderate ID (more than 60 per cent) whose EF's were significantly more impaired in comparison with children with mild ID.…”
mentioning
confidence: 99%